2022
DOI: 10.1101/2022.08.26.505378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A thousand-genome panel retraces the global spread and climatic adaptation of a major crop pathogen

Abstract: Human activity impacts the evolutionary trajectories of many species worldwide. Global trade of agricultural goods contributes to the dispersal of pathogens reshaping their genetic makeup and providing opportunities for virulence gains. Understanding how pathogens surmount control strategies and cope with new climates is crucial to predicting the future impact of crop pathogens. Here, we address this by assembling a global thousand-genome panel of Zymoseptoria tritici, a major fungal pathogen of wheat reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The integration of genome-wide markers greatly enhances the quality of pathogen monitoring by providing information about patterns of gene flow. Our study revealed only weak differentiation across Western European countries and among French regions consistent with high levels of gene flow and genetic diversity [ 55 ]. Knowledge of genetic structure can help identify recent movements of the pathogen due to natural or human-mediated dispersal.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The integration of genome-wide markers greatly enhances the quality of pathogen monitoring by providing information about patterns of gene flow. Our study revealed only weak differentiation across Western European countries and among French regions consistent with high levels of gene flow and genetic diversity [ 55 ]. Knowledge of genetic structure can help identify recent movements of the pathogen due to natural or human-mediated dispersal.…”
Section: Discussionmentioning
confidence: 75%
“…G1-G10) constituted from a mix of pure DNA from the same three isolates in different proportions (INRA10-FS1006, INRA10-FS1022, IPO-09455; Fig 4 ; Table A in S1 File ). We used existing whole genome sequencing and SNP calling data for the three isolates to assess polymorphism across the genome [ 55 ]. Using the known dilutions of pure DNA, we established the expected frequencies of reference alleles ( i .…”
Section: Resultsmentioning
confidence: 99%
“…4; Table A in Supplementary File S1). We used existing whole genome sequencing and SNP calling data for the three isolates to assess polymorphism across the genome [55]. Using the known dilutions of pure DNA, we established the expected frequencies of reference alleles (i.e.…”
Section: Reproducibility Among Replicate Assays and Recovery Of Allel...mentioning
confidence: 99%
“…Additional isolates from Oceania included 75 isolates collected in New Zealand in 2013 and 2015 [55]. A total of 154 isolates were collected in Oregon, USA, in 1990 and 2015 [22].…”
Section: Genome Sequences Used For the Design Of The Assaymentioning
confidence: 99%
“…Under co-infection, Z. tritici strains colonize wheat leaves in a mosaic of genotypes (29). Field populations exhibit high genetic and phenotypic diversity worldwide due to frequent sexual reproduction, large populations, and significant gene flow among populations (30)(31)(32). Co-infection of wheat leaves by multiple strains of Z. tritici are frequent in the field (29).…”
Section: Introductionmentioning
confidence: 99%